Study on effect of barium titanate concentration in epoxy-based composite towards dielectric material properties - Nurfarhana, Mustafa; Azahani Natasha, Azman; Ahmad Syahiman, Mohd Shah; Nurulfadzilah, Hassan; Mohamad Shaiful, Abdul Karim (Elsevier Ltd, 2024)
The properties of dielectric material can be controlled either by combining new composite materials or by altering the composition between the filler and matrix materials. This paper focuses on the development of epoxy-barium titanates composites at different filler concentrations and their relationship with dielectric properties. Epoxy resins are frequently utilized for their affordability, ability to withstand high humidity and resistance to chemicals. Meanwhile, barium titanate is recognized for its high permittivity. When these two materials are combined, they can create a high permittivity value that is advantageous for the design of small and compact antennas. In this work, five samples of different epoxy resin-barium titanate composites are made, at five different volume ratios of filler (5 vol%, 10 vol%, 15 vol%, 20 vol%, and 25 vol%). A low volume of filler results in a lower permittivity value due to the quantity of filler being less than the volume of the matrix base. Adding nano powder barium titanate to the matrix base can increase the permittivity of the composite material. However, when the volume of filler is too high, it may agglomerate, which can adversely affect the electrical performance. In this work, the complex permittivity of composite materials of epoxy resin and filler barium titanate is measured between 4 and 6 GHz using the waveguide technique. The results showed that the permittivity of epoxy-barium titanate grows continuously as the filler volume increases.